2018
DOI: 10.1016/j.carbon.2017.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Defect-mediated, thermally-activated encapsulation of metals at the surface of graphite

Abstract: We show that 3 metals -Dy, Ru, and Cu -can form multilayer intercalated (encapsulated) islands at the graphite (0001) surface if 2 specific conditions are met: Defects are introduced on the graphite terraces to act as entry portals, and the metal deposition temperature is well above ambient. Focusing on Dy as a prototype, we show that surface encapsulation is much different than bulk intercalation, because the encapsulated metal takes the form of bulk-like rafts of multilayer Dy, rather than the dilute, single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(53 citation statements)
references
References 23 publications
2
50
1
Order By: Relevance
“…We have considered the possibility that increasing D in the bending strain energy term might shift the upturn in d/h toward the right and toward better agreement with experiment. Increasing bending stiffness can be achieved by, for example, doubling the Young's modulus, Y, to 2.2 TPa in equation (8), or by adding a factor of two to the bending term in equation (9). Unfortunately, these have only a minor effect on d/h, and they enhance the downward dive in h/a with decreasing h. Neither of these changes improves agreement with experiment.…”
Section: Results Using a Model With Coupled Stretching And Bending (Smentioning
confidence: 99%
See 3 more Smart Citations
“…We have considered the possibility that increasing D in the bending strain energy term might shift the upturn in d/h toward the right and toward better agreement with experiment. Increasing bending stiffness can be achieved by, for example, doubling the Young's modulus, Y, to 2.2 TPa in equation (8), or by adding a factor of two to the bending term in equation (9). Unfortunately, these have only a minor effect on d/h, and they enhance the downward dive in h/a with decreasing h. Neither of these changes improves agreement with experiment.…”
Section: Results Using a Model With Coupled Stretching And Bending (Smentioning
confidence: 99%
“…Necessary conditions for Fe encapsulation include (i) activating the graphite surface with atomic-scale defects via Ar + ion bombardment, and (ii) depositing Fe on the activated graphite surface that is held at elevated temperature (T dep ). Our group has demonstrated that these conditions are effective for encapsulating a variety of metals, including Cu [10], Ru [11], and Dy [9]. Fe encapsulation is operational in a narrow T dep window of 875-900 K, with 900 K being the optimal temperature where the extent of encapsulation is high with minimal bare Fe on top of graphite [12].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, nucleation of additional islands will also occur preferentially at locations away from existing islands. Motivation for the above scenario comes from recent experimental studies of the deposition at around 800 K of various metals, including Cs [4], Dy, Ru, and Cu [5], on a defective HOPG surface. In these studies, HOPG was sputtered by Ar + ions to produce damage in the form of local or pointlike surface defects.…”
Section: Introductionmentioning
confidence: 99%